Pengaruh Unsur Pokok Produk Pariwisata terhadap Peningkatan Jumlah Pengunjung di Taman Wisata Matahari Cilember, Bogor - Hia, Martinus (Research and Community Service UNIVERSITAS KALBIS, 2024)
This study aims to determine the influence of the main elements of tourism on increasing the number of visitors at Matahari Tourism Park. There are four variables in this research, namely attractions, accessibility and amenities and an increase in the number of visitors. This research uses quantitative methods using random sampling techniques. Distribution of closed questionnaires to 100 respondents who were visitors to Matahari Tourism Park. The tests used in this research are validity testing, reliability testing, hypothesis testing and multiple regression analysis. The results of this research show that the variables of attraction, accessibility and amenities influence the increase in the number of visitors at Matahari Cilember Tourism Park at the same time.